Afrofuturism and Gender Consciousness in Black Panther (2018) - Nugraheni Widianingtyas (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2022)
Abstract. In the African diaspora context, Black people have never been set free from the dark history of slavery, apartheid, othering, and marginalization. The aspiration and longing for freedom, triumph, bright future or the so-called Afrofuturism conception are finally manifested in pop culture, such as in Black Panther (2018), one of the black superhero movies. Afrofuturism emerges as a way to envision a bright future despite perennial racial discrimination against Black people. Not exclusively limited to men-empowerment, this movie puts women in the spotlight and therefore also touches on the matter of gender consciousness. For those reasons, this qualitative research aims to discuss how the Black Panther movie reflects Afrofuturism and gender consciousness and how those two are interrelated. Using Paul Ricoeur's hermeneutics theory as a basis for movie interpreting, the analysis of the research relies on the writer's interpretation. The analysis results show that all of Black Panther’s prominent casts exhibit Afrocentric values by being empowered and proud of their naturally typical hair, their country with unbelievably wealth and superior technology, and who they truly are as Africans. The Afrofuturism value in Black Panther encourages black generations to go far beyond the limitations of the white imagination. Furthermore, this movie does not romanticize the idea of Black male supremacy. Black women here can be professional figures in various matters, such as love life, family, work professionalism, and service to the nation to uphold what is right for themselves, their children, nation, and communities.Keywords: Afrofuturism; Black Panther movie; black people; gender consciousnessAbstrak. Dalam konteks diaspora Afrika, orang kulit hitam tidak pernah terlepas dari sejarah kelam perbudakan, pemisahan ras, pembedaan, dan marginalisasi. Aspirasi dan kerinduan akan kebebasan, kejayaan, masa depan cerah atau yang sering disebut Afrofuturisme akhirnya terwujud melalui budaya pop, seperti Black Panther (2018), salah satu film superhero kulit hitam. Afrofuturisme muncul sebagai cara untuk membayangkan masa depan yang cerah meskipun diskriminasi rasial terhadap orang kulit hitam terus terjadi. Tak terbatas pada dominasi laki-laki, film ini banyak menyorot peran perempuan yang akhirnya menyentuh isu kesadaran gender. Oleh karena itu, penelitian kualitatif ini bertujuan untuk membahas bagaimana film Black Panther mencerminkan Afrofuturisme dan kesadaran gender serta bagaimana Afrofuturisme dan kesadaran gender saling terkait. Menggunakan teori hermeneutika dari Paul Ricouer sebagai dasar interpretasi film, analisis penelitian bergantung pada interpretasi penulis. Hasil analisis penelitian menunjukkan bahwa pemeran sentral Black Panther bersifat sangat afrosentris, misalnya, mereka bangga menunjukkan gaya rambut aslinya, negaranya dengan kekayaan luar biasa dan teknologi unggul, dan merasa berdaya dengan jati dirinya sebagai orang Afrika. Nilai Afrofuturisme dalam Black Panther mendorong generasi kulit hitam untuk melangkah jauh melampaui batasan imajinasi kulit putih. Selain itu, film ini tidak meromantisasi gagasan supremasi pria kulit hitam. Perempuan kulit hitam di film ini mampu menjadi sosok profesional dalam berbagai hal, seperti percintaan, keluarga, perkerjaan, dan pengabdian kepada bangsa untuk kemerdekaan diri sendiri, anak-anak, bangsa, dan komunitasnya.Kata kunci: Afrofuturism; film Black Panther; orang kulit hitam; kesadaran gender